RNA-seq Analysis of the SCN1A-KO Model based on CRISPR/Cas9 Genome Editing Technology. (1st February 2019) - Shi, Xiaoguang; He, Wenxin; Guo, Shanshan; Zhang, Bingying; Ren, Shuanglai; Liu, Kunmei; Sun, Tao; Cui, Jianqi
Highlights: We constructed the SCN1A knockdown cell model using CRISPR/Cas9 technology. We found that many genes have changed in the SCN1A knockout cell line. The glycolytic metabolism of cells was impaired after SCN1A knockdown. The spliceosome is closely related to the pathogenesis of Dravet syndrome. Abstract: Dravet syndrome (DS) is a disease that is primarily caused by the inactivation of the SCN1A-encoded voltage-gated sodium channel alpha subunit (Nav1.1). In this study, we constructed an SCN1A gene knockout model using CRISPR/Cas9 genome editing technology to deprive the Nav1.1 function in vitro. With mRNA-seq analysis we found abundant gene changes after SCN1A knockout, which associated with various signaling pathways, such as cancer pathways, the PI3K-AKT signaling pathway, the MAPK signaling pathway, and pathways involved in HTLV-I infection. We also noticed changes in the spliceosome, decreased glycolytic capacity, disturbances in calcium signaling pathways, and changes in the potassium, sodium, chloride, and calcium plasma channels after SCN1A knockout. In this study, we have been the first time to discover these changes and summarize them here and hope it would provide some clue for the study of Nav1.1 in the nervous system.